2015
DOI: 10.3390/en81012061
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Analysis on the Optimization of Hydraulic Fracture Networks

Abstract: Abstract:The clear understanding of hydraulic fracture network complexity and the optimization of fracture network configuration are important to the hydraulic fracturing treatment of shale gas reservoirs. For the prediction of hydraulic fracture network configuration, one of the problems is the accurate representation of natural fractures. In this work, a real natural fracture network is reconstructed from shale samples. Moreover, a virtual fracture system is proposed to simulate the large number of small fra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 37 publications
0
19
0
Order By: Relevance
“…Zou et al presented a 3D distinct element method (DEM)‐based fracturing model to investigate the mechanism of HFN propagation in naturally fractured shale formations . Zhang et al developed a displacement discontinuity method (DDM)‐based numerical model to simulate a fluid‐rock coupling system . Nagel et al used continuum and discrete element modeling approaches to simulate the geomechanical process and investigate the complex nature of the coupled interactions between a propagating hydraulic fracture and the existing natural fractures .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zou et al presented a 3D distinct element method (DEM)‐based fracturing model to investigate the mechanism of HFN propagation in naturally fractured shale formations . Zhang et al developed a displacement discontinuity method (DDM)‐based numerical model to simulate a fluid‐rock coupling system . Nagel et al used continuum and discrete element modeling approaches to simulate the geomechanical process and investigate the complex nature of the coupled interactions between a propagating hydraulic fracture and the existing natural fractures .…”
Section: Introductionmentioning
confidence: 99%
“…19 Zhang et al developed a displacement discontinuity method (DDM)-based numerical model to simulate a fluid-rock coupling system. 20 Nagel et al used continuum and discrete element modeling approaches to simulate the geomechanical process and investigate the complex nature of the coupled interactions between a propagating hydraulic fracture and the existing natural fractures. 21 Ju et al investigated the processes of the initiation and the propagation of cracks in a heterogeneous material based on the continuum-based discrete element method (CDEM) algorithm; the results indicated that material heterogeneity has considerable effect on crack initiation, but that crack propagation is controlled primarily by the geostress ratio.…”
Section: Introductionmentioning
confidence: 99%
“…Given the complexity of the problems, extensive theoretical and numerical studies on the actual kinematics of fractures propagating across interfaces between similar and dissimilar rocks have been performed by researchers all over the world [7,[10][11][12][13][14][15][16][17]. These studies of natural hydro-fractures and man-made hydraulic fractures show that the hydro-fractures are primarily branched, blunted, and/or arrested when they meet discontinuities, stress barriers and/or rock layers of strongly contrasting mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…At present, to enhance gas drainage efficiency in a low-permeability coal seam, hydraulic fracturing (HF) is used as a standard practice [1][2][3]. It achieves good results draining coal bed methane in most coal mines.…”
Section: Introductionmentioning
confidence: 99%